Organ Sales: Exploitative at Any Price?. (1st October 2012) - Lawlor, Rob
ABSTRACT In many cases, claims that a transaction is exploitative will focus on the details of the transaction, such as the price paid or conditions. For example, in a claim that a worker is exploited, the grounds for the claim are usually that the pay is not sufficient or the working conditions too dangerous. In some cases, however, the claim that a transaction is exploitative is not seen to rely on these finer details. Many, for example, claim that organ sales would be exploitative, in a way that doesn't seem to depend on the details. This article considers, but ultimately rejects, a number of arguments which could be used to defend this sort of claim.